Investigating the role of bentonite clay with different soil amendments to minimize the bioaccumulation of heavy metals in Solanum melongena L. under the irrigation of tannery wastewater - Khan, Waqas ud Din; Wei, Xiangying; Ali, Hafiz Haider; Zulfiqar, Faisal; Chen, Jianjun; Iqbal, Rashid; Zaheer, Muhammad Saqlain; Ali, Basharat; Ghafoor, Sana; Rabiya, Umm e.; Waqas, Muhammad; Ghaffar, Rabia; et al. (Frontiers in Plant Science, 2022)
Wastewater from tanneries is a major source of heavy metals in soil and plants when used for crop irrigation. The unavoidable toxicological effects of this contamination, however, can be minimized through two independent steps discussed in the present study. In the first step, a batch sorption experiment was conducted in which Cr was adsorbed through bentonite clay. For this purpose, DTPA extraction method was used to analyze Cr concentration in the soil after regular time intervals (0.5, 1, 2, 6, 8, 9, 10.5, 11.5, and 20.3 h) which reduced Cr concentration from 38.542 mgL–1 for 30 min to 5.6597 mgL–1 for 20.3 h, respectively, by applying 1% bentonite. An increase in the contact time efficiently allowed soil adsorbent to adsorb maximum Cr from soil samples. In the second step, a pot experiment was conducted with 10 different treatments to improve the physiological and biochemical parameters of the Solanum melongena L. irrigated under tanneries’ wastewater stress. There were four replicates, and the crop was harvested after 30 days of germination. It was seen that the application of wastewater significantly (P < 0.01) reduced growth of Solanum melongena L. by reducing root (77%) and shoot (63%) fresh weight when compared with CFOP (Ce-doped Fe2O3 nanoparticles); chlorophyll a and b (fourfolds) were improved under CFOP application relative to control (CN). However, the deleterious effects of Cr (86%) and Pb (90%) were significantly decreased in shoot through CFOP application relative to CN. Moreover, oxidative damage induced by the tannery’s wastewater stress (P < 0.01) was tolerated by applying different soil amendments. However, results were well pronounced with the application of CFOP which competitively decreased the concentrations of MDA (95%), H2O2 (89%), and CMP (85%) by efficiently triggering the activities of antioxidant defense mechanisms such as APX (threefold), CAT (twofold), and phenolics (75%) in stem relative to CN. Consequently, all the applied amendments (BN, BT, FOP, and CFOP) have shown the ability to efficiently tolerate the tannery’s wastewater stress; results were more pronounced with the addition of CFOP and FOP+BT by improving physiological and biochemical parameters of Solanum melongena L. in an eco-friendly way.